Real Time Blood Type Determination by Gel Test Method on an Embedded System - Enes Ayan; Erdem Kamil Yıldırım (International Journal of Applied Methods in Electronics and Computers, 2016)
This Determination of a blood type has a crucial importance for blood transfusion. Therefore it is mandatory doing tests to determine blood type before the transfusion. In order to prevent the errors in determining blood type and to save time these tests are carried out by the automatic devices. However these devices are very expensive and it is necessary to develop cheaper alternative systems. In this study, we designed a basic device which will be a first step for a cheap and fast prototype. It utilizes the image processing techniques and gel test method for real time blood type determination on embedded system. During the tests, fifty gel test cards data were used and, it is found that the proposed system can process each gel test card in 2 seconds with 99% accuracy on average.